Managed Africanized honey bees and native stingless bees increase Arabica coffee yields in southeastern Brazil - Joyce Mayra Volpini Almeida-Dias; Alistair John Campbell; Diego Moure-Oliveira; Denise Araujo Alves; Fernando Celso Longhim Quenzer; Jenifer Dias Ramos; Carlos Pamplona Rehder; Guilherme Jorge Gomes de Sousa; Andresa Aparecida Berretta; Cristiano Menezes (Scientia Agricola)
ABSTRACT Using managed pollinators to supplement the contributions of wild pollinators is a promising means to increase crop production and rural livelihoods sustainably. However, evidence of the efficacy of managed pollinators must be provided for many crops, especially in tropical regions. Herein, we introduced managed colonies, including Africanized honey bees (Apis mellifera) and native stingless bees (Scaptotrigona spp.), in 23 coffee fields across a gradient of native forest cover in southeastern Brazil. We found coffee yield per bush increased by 16 % in coffee fields near managed colonies compared to more distant control fields. We detected positive effects for both managed bee species, though with higher variability for the native bee species due to low replication. Our study provides robust evidence that supplementing coffee farms with managed bee colonies can increase coffee yields and should stimulate further research and investment in bee supplementation.